PDE based models of electric field sensors and their corresponding inverse problems - Westwood, TJ (2020)
This thesis is concerned with the forward and inverse problems associated with Electrical Capacitance Tomography (ECT) and Electrical Impedance Tomography (EIT). We collectively refer to these paradigms, and other associated modalities, as Electric Field Sensing (EFS). Common to all EFS modalities is the aim to determine the conductivity and permittivity of the material inside a volume from measurements of the electric potential and electric flux taken on the boundary of the volume. EFS modalities have many applications in industrial processes and medical diagnostics due mainly to the non-invasive, non-ionising, and non-destructive property of electric field measurements.